The Effects of Verbal Encouragement and Compliments on Physical Performance and Psychophysiological Responses During the Repeated Change of Direction Sprint Test - Sahli, Hajer; Haddad, Monoem; Jebabli, Nidhal; Sahli, Faten; Ouergui, Ibrahim; Ouerghi, Nejmeddine; Bragazzi, Nicola Luigi; Zghibi, Makrem (Frontiers in Psychology, 2022)
The general and sport psychology research is limited regarding to the difference between the effects of verbal Encouragement or compliment methods during high intensity functional exercise testing. The purpose of this study was to explore the effects of verbal encouragement and compliments on the performance of repeated change of direction sprint (RCOD) test. Thirty-six male students in secondary school participated voluntarily in the study. They were divided equally in three homogenous groups (verbal encouragement group; complement group; control group performed a standardized one repetition RCOD. The RCOD (6x20m with 25-second active recovery) test consisted of 100° change of direction at every 4m. Outcomes included performance indices (fast time; average time; total time), rating of perceived exertion (RPE), and feeling scale scores. Verbal encouragement and the compliment increased the performance indices and RPE compared to control group. In conclusion, verbal encouragement during the exercise testing would be more beneficial for optimal performance and RPE compared to compliment and control groups. However, the moods, during RCOD, reproduce more positively during compliment condition than verbal encouragement and control groups.